Results of modified thread technique for the treatment of wrist ganglion - Chaudhary, Sumedh (J Clin Orthop Trauma, 2020)
BACKGROUND: Ganglion cyst is the commonest swelling around the wrist. It usually presents as a painless swelling. There is no consensus as to the exact cause and the ideal modality of its treatment. Surgical excision has the best cure rates but has its share of complications. The aim of this study was to evaluate whether a modified thread technique can give reasonably good results with a low complication rate in patients with wrist ganglion. MATERIAL AND METHODS: One hundred and sixteen patients with wrist ganglion underwent a modified thread technique in which a sterile silk suture was passed through the ganglion, the contents of the ganglion were expressed out completely by firm pressure and the thread was tied over a sterile gauze piece forming a single loop. The thread was removed once serosanginous discharge was seen at entry point of the thread into the cyst. RESULTS: One hundred and eight patients were available for final analysis with minimum six months follow up. There was no recurrence in ninety eight patients giving success rate of ninety one percent. Recurrence was only seen in patients where complete evacuation of the contents of ganglion could not be achieved. Nine patients had minor complications in the form of superficial infection in two patients and mild pain around thread entry point in seven patients. CONCLUSION: Modified thread technique for the treatment of wrist ganglion is a minimally invasive, low cost, day care procedure which can give reasonably good results with a very low complication rate.